PERFORMANCE OF WARM MIX ASPHALT CONCRETE WEARING COURSE (AC-WC) USING ASPHALT PEN 60/70 AND SASOBITÂ® ADDITIVE - Carlina, Serli
Hot Mix Asphalt (HMA) is a type of paved mixture commonly used as flexible pavement material. However, HMA has weaknesses in terms of high mixing and compaction temperature, resulting in high CO2 and Greenhouse Gas (GHG) emissions which have a negative impact on the environment. Therefore, a type of asphalt with lower mixing and compaction temperatures is needed. One alternative that can be done is to add Sasobit® additives to the asphalt.